Pulmonary Function and Hospital Admission in Patients with Cystic Fibrosis Based on Household Second-Hand Smoking - Hassanzad, Maryam (Tanaffos, 2018)
BACKGROUND: Smoking is a known predisposing factor to exacerbations in CF patients. But the effects of second-hand tobacco smoking are not yet clear. Hence, this study determined the clinical and spirometric presentations and urinary cotinine levels among cystic fibrosis patients over seven years of age in relation to their parent’s smoking history. MATERIALS AND METHODS: In this cross-sectional comparative study, 58 consecutive cystic fibrosis patients older than seven years of age were enrolled. These patients were divided into two equal groups: those with second-hand tobacco smoking and those without. Pulmonary function tests and hospital admission rates were compared across the groups. RESULTS: The mean hospital admission times were 5.1±2.4 in the group with passive smoking, and 2.6±1.3 times in the group without (P<0.001). The cotinine level was reversely correlated to time interval passed from previous admissions (P=0.001, r=−0.432) in passive smokers and (P=0.021, r=0.314) in non-passive smokers. In the analysis of FEV1 with urine, there was a significant but negative relation between FEV1 and cotinine (P= 0.002). Besides, in the analysis of FE 25–75 and urine cotinine, there was also a significant and negative relationship (P=0.001). CONCLUSION: From our findings, we conclude that pulmonary function tests and hospital admission rate in patients with cystic fibrosis are associated with urinary cotinine level and household second-hand tobacco smoking.